Modernização urbano-citadina e representações sobre os trabalhadores na cidade de Campo Grande (décadas de 1960-70) - Moro, Nataniél Dal (2007)
The objective of the work "Urban-citizen modernization and representations about the workers in Campo Grande city (1960's and 70's) is to explain the processes trough which the representations about the urban-citizen modernization were constituted, about the workers who occupied the public space of Campo Grande downtown and to extern the representations that were prepared regarding the everyday of this common people who, in a certain way, made also the public space, a private space. Researching about this subject and writing this text consits in appointing a part of the constitutive links of the Brazilian reality as well as the history of the current Mato Grosso do Sul state, whose political and administrative capital seat is in Campo Grande city. A municipality whose population in 1960 was lower than seventy five thousand inhabitants, since in 1980 they were more than two hundred and ninety thousand people; most of them constituted by emigrants, specially emigrants from states as: São Paulo, Paraná, Minas Gerais, Bahia and Rio Grande do Sul. Not all of those emigrants, as well as a part of the local population, managed to contribute towards the called citizen progress . Then, the common people arises more as a social problem for the most diverse public and private authorities . This people, in turn, occupied territories in several ways, mainly the public spaces of Campo Grande city, in particular the sidewalks of the most busy business streets, such as 14 de Julho street and Calógeras Avenue, that never ceased to be a local symbol of modernity, that gradually were modernized. In order to analyze this reality of urban-citizen modernization and representations about the workers I used, very advantageously, the reflections of Marx, Engels, Benjamin, Bourdieu, Hobsbawm, Thompson, Williams, Chartier, Sharpe, Santos, Touraine and Faoro. The analyses of the sources and the theoretical reflections appoint that the urban-citizen modernization process highly privileged the elite from Campo Grande and that the representations about the common people and also those regarding their daily practices, as feeding, corporal hygiene and housing, were seen as unmeritorious to the progress . Therefore, the common people must not be present in the urban and commercial downtown of Campo Grande city, since they testified, material and symbolically, against the representation of progress that was being constructed, once the modernization, specially the economical modernization, was something constant during the 60's and 70's